Autumn moths and butterflies (Lepidoptera) new for the fauna of Kunashir Island - Dubatolov, V. V. (Far Eastern entomologist)
Three species, Epinotia autumnalis Oku, 2005 (Tortricidae), Deuterogonia kamonjii Fujisawa, 1991 (Oecophoridae) and Blenina senex (Butler, 1878) (Nolidae), are recorded from Russia for the first time. Thirty four moth and butterfly species are new for the fauna of Kunashir Island.